Convergence, decentralization and spatial effects: An analysis of Italian regional health outcomes. Issue 2 (February 2020) - Cavalieri, Marina; Ferrante, Livio
Highlights: Panel of 20 Italian regions over a 21-year period (1996–2016). No sigma-convergence for infant mortality rate and life expectancy at birth. Beta-convergence proves statistically significant for both health outcomes. Fiscal decentralization-convergence relationship depends on the level of regional health outcome. Spatial interactions contribute to regional convergence in health outcomes. Abstract: Fiscal decentralization has been a key component of many health sector reforms. Nevertheless, the actual effects of greater financial accountability by regional governments on reducing geographical health disparities are still debatable. The existing empirical literature is highly fragmented, focusing either on the effect of fiscal decentralization on health outcomes (without considering convergence) or on the convergence process in health (without considering decentralization). This paper aims to make a step forward by disentangling the role played by fiscal decentralization on the convergence dynamics of infant mortality rate and life expectancy at birth, considering also spatial effects. To this purpose, a panel of 20 Italian regions over the period 1996–2016 is investigated. For both our health outcomes, the results point towards no reduction in dispersion levels but evidence of a "catching-up" effect among regions. Exploiting the panel dimension of the data, fiscal decentralization seems to favour the rate of convergence of the Italian regions. However, the fiscal decentralization-growth rate relationship is sensitive to the regional level of health outcome: once high performance levels are reached, more consistent improvements require giving up a certain degree of fiscal accountability. Finally, spatial interactions appear statistically relevant for explaining the regional convergence process.